Dampak Servant Leadership Terhadap Innovative Work Behavior - Handayani, Ririn; Surya, Muhammad; Oemar , Fahmi (CV. ITTC INDONESIA, 2025)
The research was conducted at the Representative BPK of Riau Province, with the aim of testing the role of psychological empowerment and job crafting in mediating the influence of service leadership on innovative work behavior. The population of this study was 155 people. Based on this population size, in accordance with the Krejcie and Morgan (1970) table, the sample size for this study was 108 people. The sampling method used in this research is Systematic Random Sampling. All respondents will be used to obtain primary data related to the variables, which will be collected through a questionnaire with a 1-5 point Likert scale. All data obtained will be analyzed using Structural Equation Modeling (SEM) with the Smart PLS 3.0 analysis tool. This research found that service leadership has a positive effect on innovative work behavior; service leadership has a significant positive effect on psychological empowerment; Psychological empowerment has a significant positive effect on job crafting; Job crafting has a significant positive effect on innovative work behavior; Servant leadership is related to innovative work behavior through the sequential mediating effects of psychological empowerment and job crafting.